Pengaruh Perputaran Kas dan Perputaran Piutang terhadap Likuiditas pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019–2023 - Teguh Hidayat; Leony Agustina Darmansius (ARZUSIN, 2025)
Understanding the factors that influence corporate liquidity, particularly in terms of cash and receivables management efficiency, is a critical issue in managerial practice and economic decision-making. This study aims to analyze the effect of cash turnover and receivables turnover on company liquidity, measured by the Current Ratio. This is a quantitative study utilizing secondary data obtained from financial reports, articles, and journals, with a sample of 20 companies selected through purposive sampling for the 2019–2023 period. Data were analyzed using classical assumption tests, multiple linear regression, and hypothesis testing through t-tests, F-tests, and the coefficient of determination (R²). The results show that cash turnover has a significant effect on company liquidity, while receivables turnover does not have a significant effect. However, both variables simultaneously have a significant effect on the Current Ratio. These findings highlight the importance of effective cash management in maintaining corporate liquidity stability and offer practical insights for management and stakeholders in evaluating a company’s financial health.